Faktor Pengaruh Lingkungan Kerja Dan Disiplin Kerja Terhadap Kontribusi Kinerja Karyawan Pada PT. Gapura Angkasa Bandara Soekarno Hatta - Novi Cholisoh; Sendy Zul Friandi; Grees Wiliam (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2019)
Management is working with people to achieve organizational goals with the implementation of planning (planning), organizing, personnel or staffing, direction and leadership (leading), and controlling. planning, organizing, mobilizing and controlling to determine and achieve targeted goals that have been determined through the utilization of human and other resources. PT Gapura Angkasa is one of the Ground Handling companies that prioritizes customer satisfaction and loyalty where its customers are foreign and domestic airlines throughout Indonesia and to increase the profits of progress towards the company and can not be separated from qualified human resources and the role of human resources discipline is very important in the progress of the company. test results (Test f) there is a positive and significant influence between the work environment on employee performance PT. Gapura Angkasa Div Load Control of 62.9% and the remaining 37.1% explained that employee performance is influenced by other factors outside the work environment. testing the hypothesis individually (Test t) obtained the significance value of Work Discipline variable of 0.000 is smaller than 0.05 which means Work Discipline significantly influence Employee Performance. And the test results (Test f) there is a positive and significant influence between the discipline of work on the performance of employees of PT. Gapura Angkasa Div Load Control of 52.5% and the remaining 47.5% explained that employee performance is influenced by other factors the outside.